OPTIMALISASI MUATAN KONTAINER AGAR KAPAL FULL AND DOWN - Sutini -; Mokhamad Abrori (UNIMAR AMNI Semarang, 2017)
In conducting the loading to be assured that all load space can be filled by the charge (full) or the vessel can load up to a maximum laden (down) to obtain the maximum freight. However, since certain forms of gasket load, often cannot meet the cargo load space, the other possibility is way less good compaction ring, and so a lot of load space is not charged. Load space is not fully charged so-called